Comparison of staging and recurrence predictors in patients with differentiated thyroid cancer between the 7th and 8th editions of the American Joint Committee on Cancer staging systems - YAVUZ, DİLEK (My University, 2023)
Background: The predictive value of American Joint Committee on Cancer (AJCC) 8 for recurrence in differentiated thyroid cancer (DTC) is not known. We aimed to compare AJCC 7 and 8 regarding the differences in staging and recurrence predictors in DTC. Methods: Demographic, clinical (duration of disease and follow-up, the extent of surgery), laboratory (TSH, fT4, thyroglobulin, and antithyroglobulin), pathological (type of thyroid cancer, localization, multifocality, diameter, extrathyroidal extension [ETE], and lymph node [LN] metastasis), and imaging findings (sonography, and whole-body scan), and follow-up features (metastases, recurrence and/or persistence, and RAI need) were retrospectively analyzed in adult patients with DTC followed-up for at least six months. Staging was determined in accordance with AJCC 7 and AJCC 8, prediction of recurrence and persistence by ATA risk stratification, and death risk by AMES systems. The alterations in staging and recurrence predictors were analyzed. Results: A majority of study patients (N.=524) were female (N.=424) and diagnosed with papillary cancer (N.=511), the median age at diagnosis was 44. 97.89% (N.=93) of stage 2-4 patients (N.=95) in AJCC 7 were down-staged in AJCC 8. We down-staged 41 patients of 45-55 years of age into stage 1 in AJCC 8 independent of LN status. A percentage of 26.71% of patients (N.=140) did have persistence, 9.54% (N.=50) persistence at the last follow-up, and 9.54% (N.=50) had recurrence. According to AJCC 8, T4 and AMES high risk were predictors for recurrence (hazard ratio: 3.053, P=0.023; hazard ratio:2.465, and P=0.005; respectively). Both AJCC 7 and 8 were associated with recurrence (P=0.008 and P<0.001, respectively). Stage 4 in AJCC 7, and stages 3 and 4 in AJCC 8 better predicted the probability of recurrence.